The relationship between childhood trauma and mental health status among Chinese vocational high school adolescents: the mediating effect of poor self-control and internet addiction - Yuhan Su; Zhuohui Chen; Ziwei Teng; Mengdong Liu; Yuanguang Yang; Jindong Chen; Xiaoman Liu; Jing Huang (BMC, 2024)
Abstract Background Mental health problems among adolescents are a common concern globally. However, its relationship with childhood trauma is not clearly understood from the existing studies. Therefore, this study aims to explore the relationships among childhood trauma, mental health, self-control, and internet addiction in Chinese vocational high school students. Methods A cross-sectional survey was conducted among vocational high school students in China from October 2020 to December 2020. Standardized questionnaires were used to collect basic information regarding childhood trauma, self-control, psychological state, and social demographics. A structural equation model was used to study the relationships among internet addiction, self-control, childhood trauma, and mental health. Results A total of 3368 individuals participated in the study. The results revealed the mediating effects of poor self-control and internet addiction on the association between childhood trauma and mental health. Conclusions Internet addiction and low self-control play mediating roles in childhood trauma and mental health. Clarifying these relationships will help formulate better-targeted interventions to improve the mental health of Chinese vocational high school students and aid in interventions to treat and prevent mental health problems.